Flexible resource management and its effect on project cost and duration - Denis C. Pinha; Rashpal S. Ahluwalia (Journal of Industrial Engineering International, 2019)
In practice, most projects result in cost overruns and schedule slippage due to poor resource management. This paper presents an approach that aims at reducing project duration and costs by empowering project managers to assess different scenarios. The proposed approach addresses combinatorial modes for tasks, multi-skilled resources, and multiple calendars for resources. A case study reported in the literature is presented to demonstrate the capabilities of this method. As for practical implications, this approach enhances the decision-making process which results in improved solutions in terms of total project duration and cost. From an academic viewpoint, this paper adds empirical evidence to enrich the existing literature, as it highlights relevant issues to model properly the complexity of real-life projects.
Keywords: 650; Resource management; Project scheduling; Discrete event simulation; Decision support system